Impurity Diffusion at Instantaneous Outburst from a Point Source in Worst-Case Emergency Scenario Realization - O. A. Gubeladze; A. R. Gubeladze (Глобальная ядерная безопасность, 2022)
The article studies the emergency development accompanied by an explosive item explosion (burning) which contained in nuclear weapon and by a scattering nuclear fissile material into the environment. The impurity propagation simulation in atmosphere at the inactive explosion case was executed.